Teaching for Wisdom in Early Modern Education - Elżbieta Płóciennik (Ignatianum University Press, 2019)
Teaching for wisdom (especially at the early educational stages) requires personal competence by the teacher, interesting teaching aids and modern, motivational techniques that stimulate and develop the child's potential abilities and competences related to general and practical intelligence and creativity. In early education, of particular importance is the type of children's/students' activity that leads to the direct experiencing of the surrounding cultural, natural, technical and social reality. Such activity is undertaken by individuals through internal emotional involvement, which leads to the experience of values in an in-depth way, supporting development and gaining all kinds of practical experience, which in turn fosters maturity towards wisdom. The environment where Teaching for wisdom should be deliberately organized is school (preschool). Factual knowledge and the methodological competences of teachers can support the organization of educational situations that allow children/students to experience values and wisdom, develop their potential cognitive abilities, gain experience in the interpretation and evaluation of wise/unwise behaviour, and develop the habits of wise behaviour. These situations should be a source of getting students ready to use wisdom in life and to shape their value systems. The proposal of a detailed competence scope for the notion of wisdom is presented in the this article.